2017
DOI: 10.1111/tra.12533
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular vesicular transport in epithelial and endothelial cells: Challenges and opportunities

Abstract: Vesicle‐mediated transcellular transport or simply “transcytosis” is a cellular process used to shuttle macromolecules such as lipoproteins, antibodies, and albumin from one surface of a polarized cell to the other. This mechanism is in contrast to the transit of small molecules such as anions, cations and amino acids that occur via uptake, diffusion through the cytosol and release and is also distinct from paracellular leak between cells. Importantly, transcytosis has evolved as a process to selectively move … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 138 publications
(248 reference statements)
1
94
1
2
Order By: Relevance
“…Since macrophages were not involved in the antibody transfer, we next focused on the potential role of LECs in the uptake of antibodies. Certain macro molecules can be shuttled from one surface of the cell to the other by transcellular vesicular transport, i.e., transcytosis (15,(25)(26)(27)(28)(29)(30). We found that the extremely attenuated (often <200 nm in thick ness) cytoplasmic projections of sinusoidal LECs are very rich in heterogeneous cytoplasmic vesicles resembling flaskshaped cav eolae, round intracytoplasmic vesicles, and elongated tubulovacu olar structures ( Figure 7A).…”
Section: Resultsmentioning
confidence: 89%
“…Since macrophages were not involved in the antibody transfer, we next focused on the potential role of LECs in the uptake of antibodies. Certain macro molecules can be shuttled from one surface of the cell to the other by transcellular vesicular transport, i.e., transcytosis (15,(25)(26)(27)(28)(29)(30). We found that the extremely attenuated (often <200 nm in thick ness) cytoplasmic projections of sinusoidal LECs are very rich in heterogeneous cytoplasmic vesicles resembling flaskshaped cav eolae, round intracytoplasmic vesicles, and elongated tubulovacu olar structures ( Figure 7A).…”
Section: Resultsmentioning
confidence: 89%
“…34 In addition to pericytes, this buffering property may be aided by the uneven expression of proteins and enzymes involved in transcellular endothelial transport across the ICP, such as the Rho family of GTPases, the claudin family of proteins, and a broad range of cytokines, including IL-1, IL-4, IL-10, and IL-10. 35 We emphasize that the above hypotheses were not specifically investigated in the present study and require further research for clarification. Other reasons that may explain the variations in capillary circulation morphology between retinal layers may relate to their distinct role in heat exchange, retinal thermal regulation, and maintaining immune privilege.…”
Section: Discussionmentioning
confidence: 84%
“…The transport of macromolecules, including lipoproteins, across the endothelium is actively controlled by ECs via the transcellular route, or transcytosis ( 5 , 6 ). The process of transcytosis involves fluid phase or receptor-mediated ligand uptake by endocytosis, transition of the cargo through the cytoplasm, and exocytic release of the cargo ( 7 ).…”
Section: Transcytosis In Ecmentioning
confidence: 99%